Influential factors in the adherence to the certified organic production system in relation to the profile of the establishments and rural producers in Brazil - Scalco, Andréa Rossi [UNESP]; De Oliveira, Sandra Cristina; Pinto, Leonardo de Barros [UNESP] (My University, 2019)
From 2011, the adoption of the organic seal through a process of product certification is mandatory for marketing in commercial establishments in Brazil, except for sales made directly in the municipalities of origin of production. Thus, rural producers who continued to market their products in various establishments, both those located in their locality and outside it, had to comply with the new legislation. Beyond the legal aspect, there are other factors that influence the decision to obtain an organic product certificate; above all, the investments needed to be able to carry it out. In this scenario, the research conducted aimed to identify and analyze the factors that determine the adoption of organic certification in rural production in Brazil. For this purpose, it was determined whether or not there were differences in the adoption of this certification due to the type of rural establishments found, as well as the profiles of the producers analyzed. For the development of this research, a survey was conducted among 200 rural producers in Brazil who had adopted organic certification. The data were analyzed through descriptive statistics, exploratory factor analysis and hypothesis testing. The factors affecting certification identified in this survey refer to the principles of organic production, market and external groups. It should be noted that there was heterogeneity with respect to the importance of these factors as determinants of the decision to obtain certification as an organic product. Regarding the aspects referred to the characteristics of the rural establishments, the most outstanding were the state where the producer is located and the level of processing of the product. On the other hand, regarding the aspects referred to the characteristics of the producers, the level of schooling and the type of certification used stand out.
Factores determinantes de la adopción del sistema de producción orgánica certificada en relación con el perfil de los establecimientos y productores rurales en Brasil
Facteurs influençant la certification du système de production biologique et sa relation avec le profil d’établissements et des producteurs ruraux au Brésil
Keywords: Brazil; Certification; Exploratory factorial analysis; Organic certification; Organic production; Rural agriculture